Broadway musical in the space of artistic communication - Rzhevska, Maiia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of research is determined by the necessity to highlight the factors influencing the functioning of Broadway theatre as a multi-layered semiotic space that has been formed over an extended period, has undergone and continues to undergo constant transformations, by highlighting its most representative phenomenon — the musical. Main objective of the article is to characterize the Broadway musical as the core of a semiotic (communicative) artistic environment and, simultaneously, as an instrument for the realization of artistic communication. The research methodology is based on an interdisciplinary approach, the applicability of which is dictated by the specific nature of the artistic phenomenon under consideration. Results and conclusions. The study establishes that the formation of the Broadway musical occurred in parallel with the emergence and subsequent development of the urban space, which became its physical environment. The role of infrastructure development in the formation and evolution of this genre type is outlined, along with its reciprocal influences. Emphasis is placed on the unprecedentedly high concentration of artistic institutions within the Theater District of New York City. It is noted that the industry of show production and subsequent distribution involves the collaboration of numerous specialists with narrow expertise. Their composition reflects the artistic, economic, and organizational specificities of the embodiment of a musical. The study highlights the presence of a guild-like principle in the organization of the creative environment of musical theatre authors, which becomes more pronounced with the rethinking of the genre’s essence and purpose, as well as its increasing complexity (since the second half of the XXth century). Furthermore, it is stated that an essential level of information production and exchange "around the musical" is represented by music and theatre criticism and journalism, which exist in both traditional and modern forms. Various manifestations of Broadway’s inherent tendency towards self-reflection and the cultivation of historical memory are highlighted. Special attention is given to the musical Hamilton, which is considered — justifiably so — one of the pinnacle achievements of the genre. The study confirms the diversity of communicative mechanisms that shape the artistic qualities of the phenomenon, defining its unique codes while simultaneously integrating the work into a broader socio-cultural space.